Comparison of neonatal outcomes with and without the administration of betamethasone in late preterm births - Bulut, Ayça Nazlı; Cündübey, Cevat Rıfat; Ceyhan, Venhar; Aydın, Emine (Wiley, 2022)
Objective: To evaluate the effects of antenatal steroid administration on neonatal outcomes in late preterm births. Methods: Demographic and neonatal data from women who gave birth between May 2018 and March 2021 at 34+0–36+6 weeks of gestation were screened from the information system of the hospital. The patients were assigned to two groups: those who were and those who were not given steroids. All parameters were compared between the two groups. Results: The 1-minute (9 versus 8) and 5-minute (10 versus 9) Apgar scores, need for a neonatal intensive care unit (NICU) stay (23.7% versus 27.8%), length of stay (Day) in the NICU (1.97 ± 0.24 versus 2.45 ± 0.16), rate of transient tachypnea of the newborn (3.3% versus 7.8%), respiratory distress syndrome (2.5% versus 5.2%), need for mechanical ventilation (1.2% versus 3.8%), and neonatal sepsis (1% versus 2.6%) were lower in the group that received betamethasone compared with the group that did not; the differences between the two groups were statistically significant. Conclusion: Based on the results of the present study, we believe that antenatal steroid administration would be beneficial before late preterm births occurring between 34+0 and 36+6 weeks of pregnancy, considering the significant reduction in various respiratory complications, especially in respiratory distress syndrome and the need for an NICU stay.
Keywords: Betamethasone; Late Preterm; Respiratory Distress Syndrome; Transient Tachypnea of the Newborn